The Strategic Analysis of PT Bank â€œXâ€ (Persero) Tbk. Transformation : To be the most admired and progressive Financial Institution in Indonesia - Sardjono, Ardana Hendratama; Do, Anh Dung; Wicaksono, Agung (The Indonesian Journal of Business Administration, 2012)
This Study is to capture the experience overcome problems that could ruin the Bank